Determination of the Dispersion Profile in Photonic Crystal Fibers using the Empirical Relationship - Younus, Marwan Hafeedh; Ameen, Odai Falah; Ahmed, Muayad Abdullah; Kassim, Yaser Yahya (Iraqi Journal of Science, 2025)
In this work, a single-mode endless photonic crystal fiber (PCF) is proposed and theoretically analysed using the empirical relationship method. The designed PCFs are composed of three uniform rings of air holes arranged in a circular shape. Three samples of fibers (PCFsPure, PCFsdoped1 and PCFsdoped2) with the same structure but are only different in the material of core have been investigated. The guiding properties of PCFs are studied in terms of effective refractive index, confinement loss and dispersion profile. The numerical results show that the PCFsdoped2 exhibits good properties such as high refractive index, low confinement loss and red shifting in the zero dispersion compared to other samples. A red shifting in the zero dispersion, achieved in this study, may be important to generate the soliton fission. Moreover, all the designed PCFs perform a negative dispersion at higher d/Λ, which are used to obtain the coherence supercontinuum generation spectrum. The designed PCFs in this study can be used in the transmission of optical signals using different types of materials in the core structure of PCFs.